2017
DOI: 10.1007/s11418-017-1119-0
|View full text |Cite
|
Sign up to set email alerts
|

Sansoninto as evidence-based remedial medicine for depression-like behavior

Abstract: In vitro screening methods using cultured Neuro2a cells to examine the activation (phosphorylation) of extracellular signal-regulated kinase (ERK) 1/2 and promotion of neurite outgrowth revealed that the extracts of 5 Kampo (Japanese traditional) formulations have potential as medicines for the treatment of behavioral abnormalities. Since sansoninto (SAT) extract exerted stronger effects than the other candidates tested, we investigated whether its oral administration ameliorates the pathologies of some mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…SST has previously been reported to demonstrate anti-depressant effects in mice at a dose of 1000 mg/kg/day. 17 In addition, we previously reported that SST ameliorated memory impairment in dementia model rats at doses of 300 and 1000 mg/kg/day. 18 Therefore, SST300 and SST1000 were administered in experiment 1.…”
Section: Resultsmentioning
confidence: 94%
“…SST has previously been reported to demonstrate anti-depressant effects in mice at a dose of 1000 mg/kg/day. 17 In addition, we previously reported that SST ameliorated memory impairment in dementia model rats at doses of 300 and 1000 mg/kg/day. 18 Therefore, SST300 and SST1000 were administered in experiment 1.…”
Section: Resultsmentioning
confidence: 94%